Scaling up sweetpotato through agriculture and nutrition (SUSTAIN): M&E system review - Okello, J.J.; Kwikiriza, N. (International Potato Center, 2019)
The primary objectives of this monitoring and evaluation review exercise were: to assess whether the design of the SMILER forms and processes is adequate to generate reliable and quality monitoring data: this included a review of data to do spot checks on quality, consistency, and timeliness; to assess whether we have used these forms and processes consistently, and what constraints we have faced in trying to do so; to collect project managers’ views on the practicality and weaknesses of our Simple Measurement of Indicators for Learning and Evidence‐based Reporting (SMILER) system, and their recommendation for improving it; and to get project managers’ views on how to improve data handling and storage.